Understanding salinity stress responses in sorghum: exploring genotype variability and salt tolerance mechanisms - Rajabi Dehnavi, Ahmad; Zahedi, Morteza; Piernik, Agnieszka (Frontiers in Plant Science, 2024)
Salinity, a significant abiotic stressor, adversely affects global plant growth. To address this, monitoring genetic diversity within a plant species germplasm for salt tolerance traits is vital. This study investigates the responses of ten sorghum genotypes to varying salt stress levels (control, 60 mM NaCl, and 120 mM NaCl), aiming to assess genetic diversity. Using a randomized complete block design with three replications and a split-plot arrangement, salt treatments were assigned to main plots, and genotypes were placed in sub-plots. Physiological attributes, including photosynthetic rate, stomatal conductance, CO2 concentration, leaf area index, chlorophyll concentrations, and antioxidant enzyme activity, were measured during the 50% flowering stage. Fresh forage yield was evaluated at the early dough stage, while dry forage yield and sodium/potassium concentrations were determined post-drying. Salinity induced 10-23% and 21-47% reductions in forage fresh yield at 60 mM and 120 mM NaCl, respectively, across sorghum genotypes. Forage dry yield also declined by 11-33% at 60 mM NaCl and 30-58% at 120 mM NaCl. Increased oxidative stress markers, proline, soluble carbohydrates, and antioxidant enzyme activity accompanied salinity. Genotypes exhibited diverse responses, with Payam showing significant chlorophyll and yield reductions at 60 mM NaCl and notable stress indicators at 120 mM NaCl. Pegah and GS4 demonstrated robust osmoregulation. In stress tolerance indices, Sepideh excelled at 60 mM NaCl, while GS4 outperformed at 120 mM NaCl. Pegah demonstrated high tolerance at 120 mM NaCl. Our findings highlight the importance of combating oxidative stress, managing water-related stress, and maintaining ionic homeostasis for sorghum's salt stress resilience. Key indicators like K/Na ratio, MDA, MSI, SOD, and proline effectively differentiate between tolerant and sensitive genotypes, offering valuable insights for sorghum breeding. Salt-tolerant sorghum genotypes exhibit stable photosynthesis, improved stomatal function, and membrane integrity through efficient osmotic regulation and robust antioxidant enzyme activity. This capability enables them to sustain performance, minimizing final product loss. The results suggest cultivating salt-tolerant sorghum in saline areas for increased sustainable production, with Pegah and GS4 emerging as promising candidates for further testing in salt-affected environments to obtain reliable yield data.